Creating a Culture of Service. - Lotardo, Elizabeth; Earle McLeod, Lisa (linkedin.com, 2018)
Discover how to develop a service-oriented team. Learn how to communicate your purpose, emphasize your customers, and create a strategic vision to reinforce a culture of service.